CONCEPTS OF MATERIAL USE IN ARCHITECTURE IN THE 20TH CENTURY - Udom, Sutthipan; Keusombut, Jeerasak (Fine Arts Journal: Srinakharinwirot University, 2025)
Background and Objectives: The Industrial Revolution that began in the mid-18th century brought about structural changes in many dimensions, especially in terms of social and urban contexts. Rapid urbanization has resulted in an increased population density in large cities in the Western world. These changes stimulate new concepts in architectural design that focus on responding to shifting social contexts and technological advancements. This study aims to analyze the development of material concepts in architecture, emphasizing changes in perspectives towards new material usage in the context of the industrial era and their impact on modern architectural design. Methods: The study began by researching and collecting data on concepts, theories, design, and use of materials in architecture, both in pre-20th-century architecture, especially during the Industrial Revolution, and in modern architecture in the 20th century. The study examined all factors that led to design concepts and use of materials in different periods by analyzing, synthesizing, and comparing perspectives in various dimensions, such as social, artistic, and architectural aspects, including concepts regarding use of materials in architecture, between the Industrial Revolution and the modern age. The study also included examining material concepts in architecture during the Industrial Revolution and modern times to reveal the changes and influence of theories and concepts carried over from the Industrial Revolution, which led to material use concepts in the 20th century. The study concluded with an analysis of the changing role of materials in 20th-century architecture. Key Findings: The advent of the Industrial Revolution, especially the emergence of the Crystal Palace, played a significant role in shifting the public and designers’ perceptions of new material usage, especially steel and glass. These materials, which were previously considered unsuitable for architectural work, were increasingly accepted as materials reflecting technological progress, transparency, and functionality. This shift led to a change in design concepts from emphasizing historical beauty to focusing on utility and appropriateness for practical use. Implications of the Study: Materials in architecture did not only serve as structural elements, but also acted as a medium that reflected values, ideas, and discourses. Materials thus became a “language” that architects used to communicate ideas through the shape, form, and space of buildings, which was an important foundation of modern architecture in the 20th century. Conclusions and Future Research: This study suggests further research into the role of materials as a linguistic tool in architecture, especially in the contemporary context where material technology is continuously developing. As new societal discourses influence the perception and choice of materials, future directions may include comparative studies of contemporary cases where materials play a symbolic or political role, as well as studies of the relationship between materials and users experiences experiences of architectural spaces.